Robot-assisted pyeloplasty and laparoscopic pyeloplasty in children: A comparison of single-port-plus-one and multiport surgery - Chen, Jianglong; Xu, Huihuang; Lin, Shan; He, Shaohua; Tang, Kunbin; Xiao, Zhixiang; Xu, Di (Frontiers in Pediatrics, 2022)
Objective To compare the effects of different ways of trocar placement in robotic-assisted and laparoscopic pyeloplasty in children diagnosed with ureteropelvic junction obstruction (UPJO). Methods We retrospectively collected the data of 74 patients under 14 years old diagnosed with UPJO and performed robotic-assisted or laparoscopic pyeloplasty in our hospital during January 2015 and November 2021. There are four groups as follow, according to the selected surgical approaches: laparoscopic multi-port pyeloplasty (LMPY), laparoscopic single-port pyeloplasty (LSPY), robotic-assisted multi-port pyeloplasty (RMPY), robotic-assisted single-port plus one pyeloplasty (RSPY). Patients’ characteristics, perioperative and follow-up data were collected and evaluated. Results There is no significant difference in patients’ characteristics data. All of hydronephrosis Society of Fetal Urology (SFU) grade, anterior and posterior diameter of renal pelvis and ureter (APDRPU) and the differential renal function (DRF) at following time points: preoperative, post-operative and pre-post-operative, did not show difference in each group. During operation, the trocar place time, the ureteroplasty time and the whole operative time in robotic groups (RMPY and RSPY) were longer than that in laparoscopic groups (LMPY and LSPY). However, the ratio of ureteroplasty time and the whole operative time (UT/WT) in robotic groups (RMPY and RSPY) was lower than that in laparoscopic groups (LMPY and LSPY) (P=). And the blood loss volume was less in robotic groups (RMPY and RSPY) than that in laparoscopic groups (LMPY and LSPY), even there was not a statistical difference (P=0.11). There were significant differences in hospitalization day (P=) and parents’ cosmetic satisfaction scores (P=). In addition, there was no difference in fasting time, ureteral catheter containing time and postoperative complication. Conclusion Our study shows that both robotic multiple port and single port plus one approaches are comparable with laparoscopic multiple port and single port approaches in resolving the UPJO in children. And robotic approaches suggest some advantages in hospitalization time and cosmetic outcomes. Key words: UPJO, pyeloplasty, robotic, single-port